SCIDOT-06. TOWARDS EXCLUSIVELY LOCAL THERAPY OF GLIOBLASTOMA - ENGINEERING IL-12Fc WITH SUPERIOR TISSUE RETENTION AND MINIMAL SYSTEMIC EXPOSURE AFTER CNS ADMINISTRATION. (11th November 2019) - Beffinger, Michal; Schellhammer, Linda; Pantelyushin, Stanislav; Zimmermann, Iwan; Egloff, Pascal; Buch, Thorsten; Seeger, Markus; vom Berg, Johannes
Abstract: Intratumoral application of IL-12 overrides the prevailing glioblastoma (GB) associated immunosuppression and can trigger efficient anti-tumor responses. With clinical studies currently testing local expression of IL-12 in brain tumors, concerns on IL-12 systemic toxicity via leakage resurface. The fusion to an immunoglobulin heavy chain constant region ("Fc tag") should increase tissue retention of IL-12. However, export of IL-12Fc into the blood via the neonatal Fc receptor (FcRn) could nevertheless lead to systemic exposure. Subsequent systemic recycling via FcRn could lead to gradually increasing and eventually toxic serum concentrations. We analysed the effect of the Fc-tag on IL-12 tissue retention and evaluated whether FcRn also is involved in brain export and systemic recycling of IL-12Fc upon local delivery. Human or murine IL-12Fc was delivered in GB-bearing or naïve wt or FcRn-humanized mice (mFcRn-/- hFcRn tg) continuously via mini osmotic pumps or as bolus via convection-enhanced delivery (CED). Brain and blood concentration levels were assessed via ELISA. FcRn affinity of IL-12Fc mutants was assessed via ELISA and surface plasmon resonance. We observed much higher tissue retention of IL-12Fc compared to unmodified IL-12, but also an FcRn-dependent gradual increase of IL-12Fc serum levels. Testing a battery of amino acid substitutions at the FcRn interaction interface, we discovered unique substitutions that largely abolish brain export and systemic accumulation while preserving IL-12Fc functionality, leading to an over 100-fold higher brain to blood ratio than unmodified IL-12. We currently test the impact on efficacy of local IL-12Fc and checkpoint brain tumor treatment in vivo. Achieving high local concentrations at low to absent systemic exposure is an important prerequisite for a large therapeutic window for local treatment of neurologic diseases. The novel Fc-modifications present a promising platform for reducing systemic leakage of Fc-containing therapeutics in the context of continuous or intermittent CNS delivery beyond brain cancer therapy.